Odpowiedzi

Najlepsza Odpowiedź!
2009-10-02T14:10:21+02:00
-2 razy (-0,5)do kwadratu + (-2)
-------------------------------------- =
-0,1 razy [ -1,3 + 6 razy (-0,2)]

-2×(-½)² + (-2)
----------------------------- =
-0,1 × [-1,3 + 6× (-0,2)]

-2×¼ - 2
-----------------------------=
-0,1 × (-1,3 - 1,2)

-½ - 2
-------------- =
-0,1 × (-2,5)

-2½
--------- = -10
¼

2009-10-02T14:10:30+02:00
[(-2)×(-0,5)²+(-2)]/{(-0,1)[(-1,3)+6×(-0,2)]}=
= [(-0.5)-2]/[(-0,1)[-1,3-1,2]=
=-2,5/0,25=-10
2009-10-02T14:11:40+02:00
-2 razy (-0,5)do kwadratu + (-2)
-------------------------------------- =( 1²-2)/ (-0,1 razy [ -1,3-1,2]=
-0,1 razy [ -1,3 + 6 razy (-0,2)]

( -1)/ (-0,1 razy [ -2,5]=( -1)/ (+0,25]=( -1)/ 1/4=( -1)*4=-4